Epidemiology in pediatric anesthesia: a computerized survey of 10,000 anesthetics - Esener, Zeynep; Üstün, Emre (The Turkish Journal of Pediatrics, 1994)
The practice of anesthesia in 10,000 children was analysed and evaluated with the aid of Epi-Info, Version 5. There were 545 newborns, 1573 infants, 3147 children between the ages of 1 and 5 years, and 4735 children between the ages of 6 and 15 years. Female: male ratio was 1:1.9. In 92% anesthesia was provided for surgical and in 8% for diagnostic procedures. The most common sites of surgery were head and neck (19%), eye (12%), genitalia (9%) and inguinal region (8%). The type of admission was elective in 76%, emergency in 16% and outpatient in 8% of patients. The distribution within the ASA classes was 92% in I, 4% in II, 2.7% in III and 1.1% in IV + V. Premedication was given to 66% of cases. 98.5% had a general anesthetic and the remaining were given regional blocks. Induction was carried out with intravenous agents in 59% and maintenance with inhalational agents in 92%. The use of muscle relaxants was 82%, mainly succinylcholine followed by vecuronium. Endotracheal intubation was done in 86% of cases, with serious difficulties in 1.3%. 91% of the newborn babies were intubated, 2.8% with difficulty. 9.2% had blood transfusions. There were serious complications in 4.4% and 28 cardiac arrests, of which 20 were successfully resuscitated. Epi-Info, Version 5 was found satisfactory for epidemiological analysis and evaluation in anesthesia, and the information obtained with its aid was discussed in light of published data.